The cost-effectiveness of a telephone-based intervention to support caregivers of older people discharged from hospital - Youens, David (BMC Geriatr, 2019)
BACKGROUND: A telephone intervention for caregivers of older people discharged from hospital was shown to improve preparedness to care, reduce caregiver strain and caregiver distress. No cost-effectiveness analysis has been published on this, or similar interventions. The study aims addressed here were to examine whether positive outcomes for caregivers resulting from the Further Enabling Care at Home (FECH) program changed the use and costs of health services by patients; and to assess cost-effectiveness. METHODS: A single-blind randomised controlled trial compared FECH to usual care. FECH involved a specially trained nurse addressing support needs of caregivers of older patients discharged from hospital. A minimum clinically important difference in preparedness to care was defined as an increase in Preparedness for Caregiving scale score of ≥ two points from baseline. Designated data collection was at: Time 1, within four days of discharge; Time 2, 15–21 days post-discharge; and Time 3, six weeks post-discharge. A last observation carried forward approach to loss to follow-up was used, with a sensitivity analysis including only those who completed all time points. Patient use of hospital, emergency department (ED) and ambulance services were captured for 12 weeks post-discharge using administrative data. Costs included nurse time supporting caregivers, resources used by the nurse, and time taken training the nurse to deliver FECH. Cost-effectiveness was assessed using decision trees for preparedness for caregiving. RESULTS: Sixty-two intervention dyads and 79 controls provided complete data. A significantly greater proportion of intervention group caregivers reported improved preparedness to care to Time 2 (36.4% v 20.9%, p = 0.029), though this was not sustained to Time 3. The intervention cost $AUD268.28 above usual care per caregiver. No significant differences were observed in health service use between groups. The incremental cost-effectiveness ratio for each additional caregiver reporting improved preparedness to care at Time 2 was $AUD1,730.84. CONCLUSIONS: To our knowledge this is the first work to calculate the cost-effectiveness of a telephone-delivered intervention designed to support caregivers of older people post-discharge, and will support decision-making regarding implementation. Further research should examine different settings, and assess impacts on health service use with larger samples and a longer follow-up. TRIAL REGISTRATION: Australian and New Zealand Clinical Trial Registry: ACTRN12614001174673. Registered 07/11/2014.